2019
DOI: 10.1001/jamaoto.2019.2414
|View full text |Cite
|
Sign up to set email alerts
|

Association of Delayed Time to Treatment Initiation With Overall Survival and Recurrence Among Patients With Head and Neck Squamous Cell Carcinoma in an Underserved Urban Population

Abstract: IMPORTANCE Delay in time to treatment initiation (TTI) can alter survival and oncologic outcomes. There is a need to characterize these consequences and identify risk factors and reasons for treatment delay, particularly in underserved urban populations.OBJECTIVES To investigate the association of delayed treatment initiation with outcomes of overall survival and recurrence among patients with head and neck squamous cell carcinoma (HNSCC), to analyze factors that are predictive of delayed treatment initiation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
3
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 35 publications
4
75
3
7
Order By: Relevance
“…This is likely related to the known risk morbidity and mortality among patients with head and neck cancer that results from treatment delays. 7,8 In a systematic review of 51 studies, Schutte et al found that treatment delays led to reduced overall survival and disease specific survival, as well worsened functional and psychosocial outcomes. They recommended timely treatment to improve outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is likely related to the known risk morbidity and mortality among patients with head and neck cancer that results from treatment delays. 7,8 In a systematic review of 51 studies, Schutte et al found that treatment delays led to reduced overall survival and disease specific survival, as well worsened functional and psychosocial outcomes. They recommended timely treatment to improve outcomes in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…7 Similarly, in 956 patients, Liao et al found that delays in treatment led to lower overall survival and higher risk of recurrence. 8 This highlights the importance of timely intervention, even in the era of COVID-19, to maintain a high level of care. The need for timely intervention must be weighed with opposing concerns that necessitate delays or alterations in treatment paradigms to protect health care workers due to a lack of PPE or availability of preoperative COVID-19 testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations